Environmental aspects of assessment of oxbow lakes near Alsó-Tisza and Hármas-Körös based on sediment analyses results - Tamás, Margit; Farsang, Andrea (JOURNAL OF LANDSCAPE ECOLOGY, 2012)
Floodplains and oxbow lakes of the plains represent extraordinary natural and ecological values. Besides their gene preserving function, they have got a role in landscape diversity, tourism and water reserve. To let the oxbows be able to provide these functions, there is a need for continous monitoring and repair. The condition of oxbow lakes can be measured by analyzing the quality of water and sediment. During our research we appraised the status of oxbow lakes of Lower-Tisza and Hármas-Körös rivers by the quality of their surface water and bottom sediment, then we assumed the ecological status of the floodplain oxbows based on the ecological risk index defined by the Hakanson-method. According to the Hakanson ecological risk index, the floodplain oxbows of Lower-Tisza river carry a moderate potential ecological risk, while the floodplain oxbows of Hármas-Körös river can be categorized with low potential ecological risk.
Keywords: oxbow; sediment; heavy metal content; ecological risk; Lower-Tisza; Hármas-Körös